1957
DOI: 10.1107/s0365110x57002273
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of pinnoite

Abstract: The space group of pinnoite has been determined unambiguously as P42 but the reflexions for 1 = O, h+k odd, are either absent or extremely weak showing that pseudo-symmetry is present, the space group conforming closely to P42/n. The structure, obtained by making use of this pseudosymmetry and employing Patterson sections and projections, has been refined by successive twodimensional syntheses and it is found that the B atoms are tetrahedrally surrounded by O atoms and that the Mg atom is at the centre of an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1959
1959
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Both bandylite and teepleite contain isolated B(OH):;-I groups and their structures may be represented by the formulas CuB(OH).lCI and Na2B(OH)~Cl respectively [19,20,21]. Pinnoite contains anions of the form [B(OH):;OB(OHh]-2 which can be considered as resulting from condensing two B(OH):;-I groups with the elimination of H20 [22]. It is of interest to compare the spectra of these substances with those obtained in previous studies of the anhydrous borates [1] where it was found that boron in three-fold coordination could be differe ntiated by the strong ab sorption d erived from V3 of th e isolated ion s whi c h ge nerally persis ted in th e co mplex ani on.…”
Section: Borates With Simple Anionsmentioning
confidence: 99%
“…Both bandylite and teepleite contain isolated B(OH):;-I groups and their structures may be represented by the formulas CuB(OH).lCI and Na2B(OH)~Cl respectively [19,20,21]. Pinnoite contains anions of the form [B(OH):;OB(OHh]-2 which can be considered as resulting from condensing two B(OH):;-I groups with the elimination of H20 [22]. It is of interest to compare the spectra of these substances with those obtained in previous studies of the anhydrous borates [1] where it was found that boron in three-fold coordination could be differe ntiated by the strong ab sorption d erived from V3 of th e isolated ion s whi c h ge nerally persis ted in th e co mplex ani on.…”
Section: Borates With Simple Anionsmentioning
confidence: 99%
“…The accuracy and precision of the lattice-parameter ratio c/a, which mainly depends on zone-axis positions, are tested using tetragonal phases only. The crystal-structure descriptions of the ten different phases used for simulations in DynamicS are given in Paton & MacDonald (1957), Otte (1961), Wyckoff (1963), Trojer (1966), Robinson et al (1971), Wilburn & Bassett (1978), Howard et al (1991), Bideaux et al (1995) and Swope et al (1995). In addition, three Euler angles representing the crystal orientation (in Z-X-Z Bunge notation) as well as the essential experimental parameters are arbitrarily chosen for simulating the EBSD pattern of each phase.…”
Section: The Procedures Usedmentioning
confidence: 99%
“…tion between the two is not always possible and, although success has been reported in various eases using this test, it has led to negative results (Whittaker, 1953;Eriks & McGillavry, 1954;Paton & MacDonald, 1957) and even false results in a few cases (e.g., see Robertson & Shearer, 1956;Robertson, Shearer, Sim & Watson, 1958). However, if we modify the original probability distri- to distinguish between the two cases with a large margin of safety, if the test is carried out using the function P(y).…”
mentioning
confidence: 99%